1979
DOI: 10.1161/01.res.44.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Contractures and increase in internal longitudianl resistance of cow ventricular muscle induced by hypoxia.

Abstract: This study was performed to determine whether hypoxia in glucose-free solutions can increase the electrical resistance of intercellular junctions in ventricular muscle. Internal longitudinal resistance (Ri), mechanical tension, and transmembrane action potentials were measured simultaneously in cow ventricular trabeculae. The mean control value of Ri was 265 +/- 38 omegacm (mean +/- SE) at 34 degrees C. After 1 hour of hypoxia in glucose-free Tyrode's solution, it had increased by 300 +/- 41% (n = 11, P less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(71 citation statements)
references
References 30 publications
2
68
0
Order By: Relevance
“…Exposure of atria to SI at a calcium concentration of 0.5 mm caused less contracture, and less shortening of refractory periods and slowing of CV than at 2 mm CaCl2. This confirms previous findings in ventricular muscle (Hearse et al, 1977;Wojtczak, 1979;Cavero et al, 1983;Koomen et al, 1983;Fitzpatrick & Karmazyn, 1984;Anno et al, 1986;Karmazyn, 1986), although contrary findings have also been published (Nayler & Williams, 1978;Lewis et al, 1979). Why mitochondria were not protected structurally against SI at 0.5 mm calcium in the present experiments is unknown, but has been reported previously for ventricular muscle in vivo (Jennings et al, 1985a;Pilati & Paradise, 1984).…”
Section: Dijscus;onsupporting
confidence: 92%
See 1 more Smart Citation
“…Exposure of atria to SI at a calcium concentration of 0.5 mm caused less contracture, and less shortening of refractory periods and slowing of CV than at 2 mm CaCl2. This confirms previous findings in ventricular muscle (Hearse et al, 1977;Wojtczak, 1979;Cavero et al, 1983;Koomen et al, 1983;Fitzpatrick & Karmazyn, 1984;Anno et al, 1986;Karmazyn, 1986), although contrary findings have also been published (Nayler & Williams, 1978;Lewis et al, 1979). Why mitochondria were not protected structurally against SI at 0.5 mm calcium in the present experiments is unknown, but has been reported previously for ventricular muscle in vivo (Jennings et al, 1985a;Pilati & Paradise, 1984).…”
Section: Dijscus;onsupporting
confidence: 92%
“…It was of interest to discover whether sulphinpyrazone also protects the myocardium against the structural and mechanical changes produced by SI and whether other non-steroidal anti-inflammatory agents share these properties. In view of the association between calcium overload and myocardial injury (Hearse et al, 1977; Wojtczak, 1979;Koomen et al, 1983;Cavero et al, 1983;Fitzpatrick & Karmazyn, 1984;Karmazyn, 1986), the association between calcium ions and SI was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of normal/ischemia border regions in isolated preparations of the heart showed that preservation of ischemic cells by neighboring cells exposed to normal perfusion is greater in the longitudinal than in transverse direction of the fibers, consistent with ∼7-to 10-fold stronger cell-cell coupling in the longitudinal direction (45). However, under severe ischemic conditions GJ communication is blocked (46), and this blockage may limit both the spread of damage and the cell-rescuing/ preservation effect of GJs. Thus, during mild ischemia GJs remain open to preserve ischemia-affected cells, but when ischemia worsens, GJs shut down, a response that may isolate damaged areas and improve organ survival.…”
Section: Discussionmentioning
confidence: 84%
“…The extracellular voltage at local depolarization in small strips of muscle in vitro has been used to determine intracellular and extracellular resistivity of cardiac muscle (Weidmann, 1970;Clerc, 1976;Weingart, 1977;Wojtczak, 1979;Hermsmeyer, 1980). In the present study we did not determine wavefront voltage by simply measuring the voltage change during local depolarization.…”
Section: Wavefront Voltagesmentioning
confidence: 93%